Intraperitoneal ropivacaine reduces time interval to initiation of chemotherapy after surgery for advanced ovarian cancer: randomised controlled double-blind pilot study. (May 2020) - Hayden, Jane M.; Oras, Jonatan; Block, Linda; Thörn, Sven-Egron; Palmqvist, Charlotte; Salehi, Sahar; Nordstrom, Johan L.; Gupta, Anil
Abstract: Background: Advanced-stage ovarian cancer has a poor prognosis; surgical resection with the intent to leave no residual tumour followed by adjuvant chemotherapy is the standard treatment. Local anaesthetics (LA) have anti-inflammatory and analgesic effects. We hypothesised that intraperitoneal LA (IPLA) would lead to improved postoperative recovery, better pain relief, and earlier start of chemotherapy. Methods: This was a prospective, randomised, double-blind, placebo-controlled pilot study in 40 women undergoing open abdominal cytoreductive surgery. Patients were randomised to receive either intraperitoneal ropivacaine (Group IPLA) or saline (Group Placebo) perioperatively. Except for study drug, patients were treated similarly. Intraoperatively, ropivacaine 2 mg ml −1 or 0.9% saline was injected thrice intraperitoneally, and after operation via a catheter and analgesic pump into the peritoneal cavity for 72 h. Postoperative pain, time to recovery, home discharge, time to start of chemotherapy, and postoperative complications were recorded. Results: No complications from LA administration were recorded. Pain intensity and rescue analgesic consumption were similar between groups. Time to initiation of chemotherapy was significantly shorter in Group IPLA (median 21 [inter-quartile range 21–29] vs 29 [inter-quartile range 21–40] days; P =0.021). Other parameters including time to home readiness, home discharge and incidence, and complexity of postoperative complications were similar between the groups. Conclusions: Intraperitoneal ropivacaine during and for 72 h after operation after cytoreductive surgery for ovarian cancer is safe and reduces the time interval to initiation of chemotherapy. Larger studies are warranted to confirm these initial findings. Clinical trial registration: NCT02256228.